The actin cytoskeleton - Jockusch, B. M. 1939- (Advances in experimental medicine and biology ;, 2017)
"Actin is one of the most abundant proteins and ubiquitously expressed in all eukaryotes. In recent years, the analysis of structure and function of such complexes has shed new light on actin's role in cellular and tissue morphogenesis, locomotion and various forms of intracellular motility, but also on its role in nuclear processes like chromatin architecture and transcription. Progress in understanding these different physiological phenomena, but also in unravelling the basis of actin-based pathophysiological processes has been made by combining video microscopy, molecular biology, genetics and biochemistry. Thus, the current research on actin, as ongoing in many international laboratories, is a "hot spot" in basic and translational research in life sciences. In this book on "The Actin Cytoskeleton", twelve internationally renowned authors present specific chapters that cover their recent work concerned with the various roles of actin mentioned above. This comprehensive volume is therefore an attractive handbook for teachers and students in many fields of medicine and pharmacology"- Resumé vydavatel